THE EFFECTIVENESS OF THE COMBINATIONS OF CALCITRIOL AND ETHYNIL ETHYL ESTRADIOL TO DECREASE OSTEOPOROSIS AND ENDOMETRIAL CANCER RISKS IN OVARIECTOMIZED RATS - Hartiningsih Hartiningsih; Devita Anggraeni (Jurnal Kedokteran Hewan, 2017)
The objective of this research was to study the effectiveness of calcitriol and ethynil ethyl estradiol combinations to decrease osteoporosis and endometrial cancer risks in ovariectomized Wistar rats. Twenty five 8-week old female Wistar rats were randomly divided into five groups (normal controlled rats/NK, ovariectomized rats/OVK, ovariectomized rats + calcitriol supplementation/OVD, ovariectomized rats + ethynil ethyl estradiol supplementation/OVE, and ovariectomized rats + calcitriol + ethynil ethyl estradiol supplementation/OVDE). At the end of the study, all rats were weighed and euthanized with 10% ketamine and 2% xylazine. Uterus and left femur were taken and fixed in 10% formaldehyde solution for histopathological examination using hematoxylin and eosin stain. Uterus was weighed before the fixation. The results showed that the percentage of uterus weight in OVK was significantly decreased compared to NK. Meanwhile, the percentage of uterus weight in OVDE was significantly increased compared to OVK. Histopathological features of the uterus in OVK were atrophy, reduction of myometrial and endometrial layers thickness, and formation of cuboidal epithelium in the endometrial lumen. However, the thickness of myometrial and endometrial layers in OVDE were increased, and its endometrial lumen was lined with metaplastic and hyperplastic squamous cell. Histopathological features of distal femur epiphysis in OVK ras showed fewer trabecular spiculums and more adipocyte in the bone marrow compared to NK. However, OVDE had more trabecular bone spiculum and less adipocyte in the bone marrow compared to OVK. In conclusion, the combination of calcitriol and ethynil ethyl estradiol supplementation could reduce osteoporosis, but increased the endometrial cancer risk in ovariectomized Wistar rats.